The level of service quality for the public transport : a study of Rapid Kuantan in Kuantan routes - Muhammad Firdaus, Ismail (2013)
Bus transportation is one of the various means of public transportation. Its efficiency in following its route is vital to ensure customers are satisfied with the service provided. This study is conducted in Kuantan Pahang among Rapid bus passengers. The problem that had been faced by resident around kuantan is the delay the bus to get to the final destination although giving the high frequent number of buses. The objective of this study is to investigate the relationship between Service Quality dimensions (reliability, tangibility, responsiveness, assurance and empathy) and customer satisfaction among Rapid Kuantan passenger. The method that had been used to perform this study is survey method .In conducting this study, initial observation was conducted to identify the parameter. Then, a set of questionnaires was distributed to bus passengers in order to tap into the satisfaction parameters. The data was analyzed with SPSS to find the outcome if there have a relationship between service quality and customer satisfaction. From the result the relationship between the dependent variable (customer satisfaction) and the dimensions of service quality (reliability, tangibility, responsiveness, assurance, empathy) were statistically significant. The results also show that there was medium relationship between perceptions of servqual and dependent variable (customer satisfaction). Therefore, the customer perceptions of service quality and customer satisfaction at Rapid Kuantan were significantly linked. The result is beneficial for relevant authorities in developing effective measure for better bus performance.